Performance of Makerless Tracking for Gimbaled Dynamic Tumor Tracking - Ziegler, Marc; Lettmaier, Sebastian; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2019)
Background and Purpose: The purpose of this work is to report the workflow and the accuracy of the new markerless dynamic tumor tracking (MLDTT) method of the Vero 4DRT system introduced with ExacTrac 3.6.1. Material and Methods: Phantom measurements were performed to assess the accuracy of the MLDTT algorithm by using the QA-tool which is provided by the vendor. A patient breathing curve was used as the motion trajectory of the phantom and the target positions detected by the MLDTT algorithm were compared to the defined positions. Furthermore, eight patients have been treated with MLDTT between May 2018 and July 2019. A log-file analysis is used to evaluate MLDTT treatment data. Results: The accuracy of the MLDTT detection is 0.12 mm ± 0.12 mm, 0.12 mm ± 0.11 mm, 0.20 mm ± 0.21 mm for the x-, y-, z-direction, respectively. These values are comparable to the accuracy of marker based DTT at the Vero system. The median treatment time was 21 min 34 seconds and 175 kV images were acquired during treatment for monitoring the target motion. Conclusion: The accuracy of the MLDTT algorithm is comparable to the marker based approach and the accuracy reported for the XSight Lung of the CyberKnife. Eight patients were treated successfully using MLDTT and the treatment times are comparable to a standard DTT treatment.
CRIS-Team Scopus Importer:2019-12-27
Keywords: NSCLC; Real-time monitoring; Stereotactic body radiation therapy; Tumor Tracking